An energy-aware active smart card. - Tessier, R. (IEEE Transactions on VLSI systems)
Despite recent advances in smart card technology, most modern smart cards continue to rely on card readers for power and clocking, creating a potential security gap. In this paper, we present an energy-aware smart card architecture that operates using an embedded battery and crystal. This low-power VLSI system is continually active and provides enhanced security through periodic internal update when the card is detached from a reader. Our architecture achieves reduced power consumption by deactivating the majority of its circuitry, including an embedded microcontroller, for the vast majority of the card's lifetime. A proof-of-concept prototype implementation of the architecture has been developed including register-transfer-level and gate-level designs which have been synthesized to silicon. To permit extended operation for up to 18 months, critical design logic has been implemented using ultralow-power (adiabatic) circuit techniques.